An innovative continuous flow BNR-IC process for nutrients removal and phosphorus recovery from synthetic and real domestic wastewater - Zou, Haiming; Lu, Xiwu (Journal of Environmental Engineering and Landscape Management, 2016)
An innovative continuous flow process linking biological nutrients removal (BNR) with induced crystallization (IC) was used to remove nutrients and recover phosphorus (P) from synthetic and real domestic wastewater. The results showed that a good nutrients removal performance was found regardless of feeding solutions. P recovery efficiency from synthetic wastewater was 70.2% slightly less than that from real domestic sewage (74.2%). Importantly, P recovery can effectively enhance the subsequent biological P removal. Polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) analysis displayed an obvious shift in microbial community structure when switching feeding synthetic solution to real wastewater. A total of 13 bands were detected in sludge samples using synthetic and real domestic sewage, affiliated with 8 phyla or classes domain Bacteria (Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Flavobacteria, Actinobacteria, Sphingobacteria, Epsilonproteobacteria and Chlorobia). The results obtained here suggest that the continuous flow BNR-IC process is feasible for nutrients removal and P recovery from domestic sewage and is a promising technology for wastewater treatment combined with recycling of P elements.